1977
DOI: 10.1128/aac.11.1.174
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Cephalosporins in Horse Serum

Abstract: The antibiotic activity of cephalothin, cephaloridine, cephalexin, cephaloglycin, cefazolin, and cefamandole was determined after storage for up to 30 days in horse serum at -10 and 4°C. Cephalothin, cefamandole, cefazolin, and cephalexin were stable for at least 30 days at -10°C, whereas cephaloridine lost 29% of its initial activity and cephaloglycin lost more than 50%. Cefamandole, cefazolin, and cephalexin could only be stored for 3 days at 400 without significant loss in activity, whereas cephalothin, cep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1977
1977
1987
1987

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…It was recently reported that cephalothin shows a significant loss in potency when held at 4°C in horse serum (1). Furthermore, Fleming and Markowsky have shown that cephalothin lost 56% activity after 6 h of incubation at 370C (Program Abstr.…”
mentioning
confidence: 99%
“…It was recently reported that cephalothin shows a significant loss in potency when held at 4°C in horse serum (1). Furthermore, Fleming and Markowsky have shown that cephalothin lost 56% activity after 6 h of incubation at 370C (Program Abstr.…”
mentioning
confidence: 99%